THE EFFECT OF HEURISTIC STRATEGIES AND CRITICAL THINKING ABILITY ON STUDENT LEARNING OUTCOMES OF THE VALUES OF PANCASILA ON PPKN SUBJECTS CLASS VI SD SWASTA HKBP 2 SIDORAME, MEDAN - Santy Manalu; Deny Setiawan; Daulat Saragi (SENSEI RESEARCH CENTER, 2021)
This study aims to determine: 1) The influence of heuristic learning strategies and expository learning strategies on student learning outcomes, 2) The influence of critical thinking skills on student learning outcomes. 3) The interaction between heuristic learning strategies and critical thinking skills on student learning outcomes. This study used a quasi-experimental research method. The research was conducted from April to May 2021.The population of this study were students of class VI SDS HKBP 2 SIDORAME Medan with a total of 50 students. The sample is the VIA class with 26 students as the experimental class and the VIB class with 24 students as the control class. The data collection technique used a critical thinking ability questionnaire and a learning outcome test. The data analysis technique used two-way analysis of variance. The results of the study are as follows: (1) There are differences in learning outcomes students who were taught with heuristic learning strategies with an average value of 86.15 higher than the learning outcomes of students taught with expository learning strategies with an average of 76.39, the results of the analysis of variance showed that the Fcount value was 3,795> the Ftable value was 3.19 and the probability value or significance of 0.08 <0.05, so that H0 is rejected; (2) There is a significant difference between student learning outcomes with high critical thinking skills and the average88,409and students who have low critical thinking skills on average 68,133. Result of analysis of variance obtained Fcount value of 90.448> Ftable value of 3.19 and significant value 0.00 <0.05, so H0 is rejected; (3) There is an interaction between heuristic learning strategies and students critical thinking abilities in improving student PPKn learning outcomes, the results of analysis of variance Fcount value of 4.134> Ftable value of 3.19 and a significance of 0.006 <0.05, so H0 is rejected.